2011
DOI: 10.1007/s10522-011-9349-0
|View full text |Cite
|
Sign up to set email alerts
|

It’s not all equal: a multiphasic theory of thymic involution

Abstract: Regression of the thymus is a key feature of immunosenescence, which coincides with a decrease in T cell output and contributes to the restriction of the T cell repertoire in the elderly, leading to increased susceptibility to illness and disease. However, the mechanisms involved in thymic involution are still not fully known. Although, it is often believed that thymic involution occurs during the onset of puberty, increasing data suggests alterations to the thymus happen much earlier in life. Therefore, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…Indeed, several studies using a variety of thymic indices (cellularity, epithelial space, number of recent thymic emigrants) have observed that thymic involution occurs early in life, prior to puberty and that the rate of decline is not linear, but appears to be phasic. In mice, thymic cellularity begins to decrease within the first few weeks after birth (37, 45, 53, 85) and a similar picture is evident in human (51, 52, 86), equine (87), and zebrafish (88) thymus.…”
Section: Kinetics Of Age-associated Thymic Involutionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, several studies using a variety of thymic indices (cellularity, epithelial space, number of recent thymic emigrants) have observed that thymic involution occurs early in life, prior to puberty and that the rate of decline is not linear, but appears to be phasic. In mice, thymic cellularity begins to decrease within the first few weeks after birth (37, 45, 53, 85) and a similar picture is evident in human (51, 52, 86), equine (87), and zebrafish (88) thymus.…”
Section: Kinetics Of Age-associated Thymic Involutionmentioning
confidence: 73%
“…Indeed, the onset of thymic involution occurs much earlier than most acknowledged features of aging and interestingly, microarray analysis of the aged thymic revealed limited overlap with genes normally associated with aging (7). Thus, we propose that there are at least two phases in thymic involution: the first occurring in early life which would be referred to as “growth-dependent thymic involution,” as it is associated with this period of physiological growth and development and another termed “age-dependent thymic involution” linked to the age-related changes that are occurring in various body systems (85). …”
Section: Kinetics Of Age-associated Thymic Involutionmentioning
confidence: 99%
“…Therefore it cannot be simply considered an aging phenomenon, but, more likely, the result of tightly regulated mechanisms many of which are still elusive (Aronson 1991;Aw and Palmer 2012). Even within mammals, thymic involution seems to follow different patterns.…”
Section: Thymic Maturation or Thymic Involution: A Process Far Beyondmentioning
confidence: 99%
“…Thymic weight has been shown to increase in dogs between 1 and 6 months of age [32], after which time a reduction in thymic weight seems to correlate with atrophy of the thymic cortex in dogs up to 2 years of age [33], but longitudinal studies of dogs beyond this age are lacking. However, similarities between the profile of sj-TREC in Labrador retriever dogs and that seen in other species suggests that the canine thymus is likely to demonstrate the same the same multi-phasic involution observed in other vertebrates [34]. Thus adding further to the evidence that the age-related decline of the thymus is an evolutionary conserved event [4].…”
Section: Discussionmentioning
confidence: 99%